2020
DOI: 10.1148/ryai.2020200079
|View full text |Cite
|
Sign up to set email alerts
|

Automated Assessment and Tracking of COVID-19 Pulmonary Disease Severity on Chest Radiographs Using Convolutional Siamese Neural Networks

Abstract: Purpose To develop an automated measure of COVID-19 pulmonary disease severity on chest radiographs (CXRs), for longitudinal disease tracking and outcome prediction. Materials and Methods A convolutional Siamese neural network-based algorithm was trained to output a measure of pulmonary disease severity on CXRs (pulmonary x-ray severity (PXS) score), using weakly-supervised pretraining on ∼160,000 anterior-posterior images from CheXpert and transfer learning on 314 fron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
155
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 126 publications
(160 citation statements)
references
References 27 publications
4
155
0
1
Order By: Relevance
“…The Fleiss κ for three thoracic radiologists using the PXS-updated AI system was 0.74 ( Fig 1 B). We found that these severity categories were significantly associated with subsequent intubation or death within 3 days of admission in 142 CXRs for patients (from the 154 CXR cohort) without an endotracheal tube on the admission CXR, which was a subset of previously published clinical outcomes data from hospitalized patients with COVID-19 ( 5 ) ( Table 2 ). A CXR with a normal/minimal grade had an odds ratio significantly below 1, while CXRs with moderate or severe grades had odds ratio significantly greater than 1, for both the PXS-original and PXS-updated systems.…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…The Fleiss κ for three thoracic radiologists using the PXS-updated AI system was 0.74 ( Fig 1 B). We found that these severity categories were significantly associated with subsequent intubation or death within 3 days of admission in 142 CXRs for patients (from the 154 CXR cohort) without an endotracheal tube on the admission CXR, which was a subset of previously published clinical outcomes data from hospitalized patients with COVID-19 ( 5 ) ( Table 2 ). A CXR with a normal/minimal grade had an odds ratio significantly below 1, while CXRs with moderate or severe grades had odds ratio significantly greater than 1, for both the PXS-original and PXS-updated systems.…”
Section: Resultsmentioning
confidence: 73%
“…A published test cohort of 154 admission CXRs from 154 unique patients hospitalized with COVID-19 at Massachusetts General Hospital (Boston, Massachusetts) at least in part from March 27, 2020 to March 31, 2020 was used, with patient characteristics summarized in this previous work ( 5 ). Quantitative lung disease severity scores (PXS scores) were calculated for the frontal view pixel data DICOMs using previously reported deep learning-based models, PXS-original ( 5 ) and PXS-updated ( 6 ). The updated model is a version of the former tuned on additional outpatient CXR data, with improved performance compared to the original model that was trained on hospitalized patients.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, laboratory tests and chest radiographs have become critical tools in documenting disease severity and monitoring progress and treatment outcomes. We determined that bilateral pneumonia with a high mRALE score calculated based on the type and extent of chest radiographic involvement may also be one of the indicators of poor prognosis [ 21 , 22 ]. It should be noted that multiple antibiotics administration did not change the course and outcome of the disease.…”
Section: Discussionmentioning
confidence: 99%